An A2 β-casein infant formula with high sn-2 palmitate and casein phosphopeptides supports adequate growth, improved stool consistency, and bone strength in healthy, term Chinese infants: a randomized, double-blind, controlled clinical trial - Sheng, Xiao-Yang; Mi, Wiola; Yuan, Qing Bin; Liu, Bryan Yanwen; Carnielli, Virgilio; Ning, Yi Bing; Einerhand, Alexandra W. C. (Frontiers in Nutrition, 2024)
The aim of this randomized, double-blind, controlled trial was to examine the effects of infant formula on the growth, stool consistency, and bone strength of infants (n=120) over a period of four months. The investigational group was fed an A2 β-casein cow's milk infant formula containing casein phosphopeptides (CPP) and high sn-2 palmitate (54% of total palmitate at sn-2). The control group was fed a standard cow's milk formula without CPP and with low sn-2 palmitate (29% of total palmitate at sn-2). The third group was fed human milk (HM) (n=60). All three groups had similar baseline characteristics, and maintained similar BMI, sleep habits, and growth rates in body weight and length throughout the study. However, compared to the control group, infants in the investigational and human milk groups had significantly: i) greater body length at 90, 120, and 150 days of age; ii) greater growth rate in head circumference from 30 to 60 days of age, with larger head circumference at 60 days of age; iii) larger daily stool frequency at 60, 90, and 120 days of age; iv) softer stool at 60, 90, and 120 days of age; v) higher bone quality index and bone speed of sound at 150 days of age; vi) fewer hours of crying at 60 and 90 days of age; vii) less abdominal distention, burp, and flatus at 60, 90, and 120 days of age; and viii) less constipation at 90 days of age. At other time points, no significant differences were observed between the three groups. No serious adverse events (AEs) related to the study products were reported, and significantly fewer infants in the investigational and HM groups experienced at least one AE compared to the control group. The study suggests that the A2 β-casein formula with high sn-2 palmitate and CPP supports adequate growth, is well tolerated, and may have beneficial effects on stool consistency, gastrointestinal comfort, crying duration, and bone density, comparable to HM.